2019
DOI: 10.1186/s12879-019-4344-1
|View full text |Cite
|
Sign up to set email alerts
|

Linkage to hepatitis C care after incarceration in jail: a prospective, single arm clinical trial

Abstract: Background Hepatitis C virus (HCV) is a major public health problem in correctional settings. HCV treatment is often not possible in U.S. jails due to short lengths of stay. Linkage to care is crucial in these settings, but competing priorities complicate community healthcare engagement and retention after incarceration. Methods We conducted a single arm clinical trial of a combined transitional care coordination (TCC) and patient navigation intervention and assessed th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 37 publications
3
48
1
Order By: Relevance
“…These ndings highlight the signi cant impact of prison release on treatment response assessment and its interpretations. The ITT SVR among former inmates who initiated treatment in community was similar to a recent study from New York City jails (45% vs. 41%); however, mITT SVR in our study was higher compared to their observed cure rates for community initiates (100% vs. 78%) (15). These ndings may suggest a lower risk of reinfection or treatment failure in the Iranian community compared to the United States.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These ndings highlight the signi cant impact of prison release on treatment response assessment and its interpretations. The ITT SVR among former inmates who initiated treatment in community was similar to a recent study from New York City jails (45% vs. 41%); however, mITT SVR in our study was higher compared to their observed cure rates for community initiates (100% vs. 78%) (15). These ndings may suggest a lower risk of reinfection or treatment failure in the Iranian community compared to the United States.…”
Section: Discussionsupporting
confidence: 83%
“…There is a growing body of evidence on successful transitional programs to engage patients with healthcare services after release -mainly conducted by community-based providers and NGOs-ranging from reminder calls to intensive case management (36). Three studies from the United States have reported that only one-quarter of patients who returned to the community were linked to HCV care after incarceration (15,37,38). However, we showed that more than two-thirds of patients could be linked to care following release, highlighting the critical role of active patient navigation in engaging patients with post-release care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simplified treatment algorithms [ 41 ] along with expanded eligibility criteria for 8-week treatment regimens [ 42 ] should be leveraged when clinically appropriate to allow more individuals to be treated in jail with shorter stays. Patient navigation strategies that have demonstrated early effectiveness in our setting [ 9 ] should be further evaluated and scaled up to improve treatment outcomes when patients are discharged from jail.…”
Section: Discussionmentioning
confidence: 99%
“…Challenges to HCV treatment in jails include short and unpredictable lengths of stay (median 19 days for admissions to NYC jails during 2018) [ 8 ] and low rates of linkage to community care after discharge (range, 9%–31%) [ 9 , 10 ]. Treatment in prisons has scaled up in a number of states, but gaps remain (range, 0.1%–28.4% of HCV-infected persons treated per year) [ 11 ].…”
mentioning
confidence: 99%